Wildlife as Sentinels of Antimicrobial Resistance in Germany? - Plaza-Rodríguez, Carolina; Alt, Katja; Grobbel, Mirjam; Hammerl, Jens Andre; Irrgang, Alexandra; Szabo, Istvan; Stingl, Kerstin; Schuh, Elisabeth; Wiehle, Lars; Pfefferkorn, Beatrice; Naumann, Steffen; Kaesbohrer, Annemarie; et al. (Frontiers in Veterinary Science, 2021)
In the framework of the German National Zoonoses Monitoring Program, samples from wild boars, cervids and wild birds were collected nationwide. Fecal samples were tested for the presence of Salmonella spp. (in wild boars and wild birds), Campylobacter spp. (in cervids and wild birds), Shiga toxin-producing Escherichia (E.) coli (STEC), commensal E. coli and extended-spectrum beta-lactamase- (ESBL) or ampicillinase class C (AmpC) beta-lactamase-producing E. coli (in wild boars, cervids and wild birds). In addition, the presence of methicillin-resistant Staphylococcus aureus (MRSA) was investigated in nasal swabs from wild boars. AMR was assessed according to epidemiological cut-offs provided by EUCAST. Salmonella spp. were isolated from 13 of 552 (2.4 %) tested wild boar fecal samples, but absent in all 101 samples from wild birds. Nine of the eleven isolates that were submitted to the NRL Salmonella were susceptible to all tested antimicrobial substances. Campylobacter spp. were isolated from four out of 504 (0.8 %) roe deer fecal samples, but not from any of the wild bird samples. Of the two isolates received in the NRL Campylobacter, neither showed resistance to any of the substances tested. From roe deer, 40.2 % of the fecal samples yielded STEC compared to 6.9 % from wild boars. In wild birds, no STEC isolates were found. Of 150 STEC isolates received in the NRL (24 from wild boars and 126 from cervids), only one from each animal species showed resistance. None of the 577 nasal swabs from wild boars yielded MRSA. Of the 219 isolates of commensal E. coli from wild boars tested for AMR, 210 were susceptible to all 14 tested substances (95.9 %). In roe deer this proportion was even higher (97.8 %), whereas in wild birds this proportion was lower (83.7%). Nevertheless, selective isolation of ESBL-/AmpC-producing E. coli yielded 6.5 % positive samples from wild boars, 2.3 % from roe deer and 9.8 % from wild birds. Among the 25 confirmed ESBL-/AmpC-producing isolates from wild boars, 14 (56.0 %) showed resistance up to five classes of substances. This proportion was lower in roe deer (25 %) and higher in wild birds (70 %).